Association between Stroop tasks and heart rate variability features in patients with somatic symptom disorder. (April 2021) - Huang, Wei-Lieh; Liao, Shih-Cheng; Gau, Susan Shur-Fen
Abstract: Objective: Patients with somatic symptom disorder (SSD) may have declined parasympathetic activity and selective attention to negative information. We combined Stroop tasks and heart rate variability (HRV) measurements to explore the brain mechanism of SSD. Methods: 104 SSD patients (64 women) and 100 healthy adults (76 women) received three Stroop tasks (the "cognitive" color-word Stroop, "emotional" emotion Stroop, and "cognitive and emotional" face-word Stroop) with low and high interference conditions. The key HRV indexes included high-frequency power (HF) and standard deviation of normal to normal RR intervals (SDNN). The generalized estimating equation model was used to examine the effects of SSD on three Stroop tasks performance (accuracy and reaction time) and HRV (HF and SDNN) controlling for sex, age, body mass index, and the levels of anxiety and depression. Results: For Stroop tasks, the significant group difference in emotion Stroop task with the high level of interference (SSD patients had lower accuracy than healthy ones) was only found in women. As for HRV, only men during color-word Stroop, women during emotion Stroop revealed significant between-group differences; SDNN in SSD men was higher than healthy men, and HF in SSD women was lower than healthy women controlling for the confounding factors. The significantly longer reaction time in SSD women than in healthy women diminished in the adjusted analysis. Conclusion: Emotion Stroop task and HRV helps distinguish SSD patients from healthy adults, particularly in women. Sex-specific measures for early detection and intervention for SSD are suggested. Highlights: Women with SSD revealed lower HF and less accuracy in emotion Stroop with high interference than healthy women. During color-word Stroop with high interference, SDNN was higher in men with SSD than in healthy men. Emotion Stroop task and HRV help distinguish SSD patients from healthy adults. The magnitude of longer reaction time in SSD women than healthy women diminished after controlling depression/anxiety.